Reducing the energy demand of bioethanol through salt extractive distillation enabled by electrodialysis - Hussain, Mohammed (Kansas State University, 2011)
The expanded Renewable Fuel Standard (RFS2), established under the Energy Independence and Security Act (EISA) of 2007, mandates the production of 136.3 GL/year of renewable fuels in the U.S. in 2022: 56.8 GL/year of corn-ethanol, 60.6 GL/year of second generation biofuels such as cellulosic ethanol, and 18.9 GL/year of advanced biofuels such as biomass-based diesel. One of the several challenges when a biochemical conversion technique is used to produce bioethanol from corn and cellulosic feedstock is the high energy demand for recovering and purifying ethanol, which is mainly due to the low concentration of ethanol in the fermentation broth and the challenging water-ethanol vapor liquid equilibrium. Dilute ethanol from the fermentation broth can be separated and concentrated aided by salt extractive distillation to directly produce fuel ethanol leading to significant energy savings. Techniques other than highly energy intensive evaporative salt concentration/crystallization and solids drying for recovering salt, which is used to facilitate distillation, have rarely been considered. In this study, a novel combination of electrodialysis and spray drying was investigated to recover the salt. Salt extractive distillation – with salt recovery enabled by electrodialysis – was conceptually integrated in the fermentation broth-ethanol separation trains of corn and cellulosic ethanol facilities and investigated through process simulation with Aspen Plus® 2006.5 to reduce the recovery and purification energy demand of bioethanol. Experiments for the electrodialytic concentration of calcium chloride from high diluate concentrations, prevalent in the salt recovery process when calcium chloride is used as the salt separating agent in the salt extractive distillation of bioethanol, were carried out to determine the fundamental transport properties of an ion exchange membrane pair comprising commercially available membranes for implementation in the conceptual process designs. The maximum calcium chloride concentration achievable through electrodialytic concentration is 34.6 wt%, which is mainly limited by the water transport number. In case of corn-ethanol, retrofitted salt extractive distillation resulted in an energy demand reduction of about 20% and total annual cost savings on the order of MM$0.5 per year when compared with the state-of-the-art rectification/adsorption process for producing fuel ethanol from the beer column distillate. In case of cellulosic ethanol, salt extractive distillation with direct vapor recompression provided the highest energy savings of about 22% and total annual cost savings on the order of MM$2.4 per year when compared with the base case comprising conventional distillation and adsorption for recovering and purifying ethanol from the fermentation broth. Based on the conceptual process design studies, an overall maximum energy savings potential of 1.5*10[superscript]17 J or about 0.14 Quad (as natural gas higher heating value) per year could be estimated for the targeted 56.8 GL of corn-ethanol and 60.6 GL of cellulosic ethanol to be produced in the U.S in 2022 when salt extractive distillation enabled by electrodialysis is implemented in the fermentation broth-ethanol separation trains of the corn and cellulosic ethanol facilities.
Keywords: Bioethanol; Salt extractive distillation; Fuel ethanol; Electrodialytic concentration; Chemical Engineering (0542); Engineering (0537)